Peran Lazismu Dalam Upaya Meningkatkan Kesejahteraan Sosial Bagi Pelaku Usaha Mikro Kecil Menengah (UMKM) di Kota Medan - Abdul Majid; Efendi Augus (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2023)
This study aims to determine the role of Lazismu in efforts to improve social welfare for Micro, Small and Medium Enterprises (UMKM) in Medan City. This research method uses a qualitative research method with a descriptive approach). Data collection techniques through observation, interviews, documentation, and literature study. From the results of research conducted by researchers, the level of social welfare of UMKM actors who have been assisted by Lazismu Medan City can be said to fulfill their daily household income and benefit from their business, provide employment, the health conditions of the perpetrators have BPJS in class 2 and class 3, some have received free assistance from the government, and some do not have it, then for the level of children's education it is still good and running even though some have school constraints, both entrance fees, constrained, covid, constrained payment of tuition fees and constrained by the distance of the school. In addition, the author also suggests that catering UMKM players enter their business online so that there are more customers and a lot of interest.